MENINGKATKAN MINAT DAN PRESTASI BELAJAR TENTANG FPB DAN KPK MELALUI STRATEGI PEMBELAJARAN EKSPOSITORI - Ika Septi Hidayati; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2016)
The subject of this study is the fourth grade students of SD Negeri Prembulan, with 28 students. Data collected by observation, questionnaires, tests, and documentation. The results showed that interests and mathematics achievement increased. The percentage interest Based on the results of questionnaires interest in mathematics learning his average percentage is 84% which is very high and is categorized based observers made from cycle to cycle increased. In the pre-cycle average value was 67.71 class of 15 students who achieve KKM, KKM attainment percentage is 53.57%. In the first cycle average rose 9.56 points and the average value of 77.27 in the first cycle classes with 18 students who achieve KKM, KKM attainment percentage of 64%. In the second cycle average rose 9.63 points is equal to 86.90. In the second cycle by 23 students reached the KKM, percentage achievement of 82% KKM. By the results of studies conducted, researchers advise teachers can implement strategies expository as a variation model of learning.